Jazz, rock, and rebels : cold war politics and American culture in a divided Germany - Poiger, Uta G., 1965- (Studies on the history of society and culture, 2000)
In the two decades after World War II, Germans on both sides of the iron curtain fought vehemently over American cultural imports. This book traces how westerns, jeans, jazz, rock 'n' roll, and stars like Marlon Brando and Elvis Presley reached adolescents in both Germanies, who eagerly adopted the new styles. It reveals that East and West German authorities deployed gender and racial norms to contain Americanized youth cultures in their own territories and to carry on the ideological Cold War battle with each other.